Peningkatan Hasil Belajar Luas Trapesium dan Layang-layang dengan Model Cooperative Learning tipe Jigsaw di SD - Rahmadia, Della; Masniladevi, Masniladevi; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
The purpose of this research was to improve the learning outcomes of extensive trapeziodal and kite by using Cooperative Learning type Jigsaw of 5th grade elementary school’s students. Type of this research was classroom action research with qualitative and quantitative approach. Subjects of this research were students of 5th grade were 24 people of 10 boys and 14 girls. Research conducted in two cycles with research procedure included of planning, implementation, observation, and reflection. The result of research was improve a) Lesson plan of the cycle of I was 83,9% and lessen pland of the cycle II was 92,86%, b) The implementation of teacher’s activity of  cycle I was 87,49% and cycle II was 92,86% while the implementation student’s activity of cycle I was 82,1% and cycle II was 92,86%, c) the student’s learning outcomes in the cycle I was 75,06 and cycle II was 88,95. The conclusion of this research was the using of Cooperative Learning model type Jigsaw can improve students achievement in learning extensive trapeziodal and kite  of 5th grade at SDN 39 Pasar Ambacang Kota Padang.Keyword : Learning outcomes, Cooperative Learning, Jigsaw